2023
DOI: 10.3389/fnut.2023.1218538
|View full text |Cite
|
Sign up to set email alerts
|

The effects of olive oil consumption on cognitive performance: a systematic review

Asra Fazlollahi,
Kimia Motlagh Asghari,
Cynthia Aslan
et al.

Abstract: IntroductionThe Mediterranean diet is marked by the regular intake of olive oil, which may play a role in preventing and protecting against cognitive deterioration and dementia. The strength of these effects have been examined by several recent randomized controlled trials (RCTs), but their findings have not been consistent. In light of this inconsistency, the present study performed a systematic review to examine the relationship between the consumption of olive oil and cognition.MethodsThe Web of Science, Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…As we can observe, world production has doubled. This is due to the balanced composition of the oil and its link with greater longevity and lower cardiovascular disease rate, cancer and age cognitive decline [44][45][46]. The trend in international production is marked by Spanish production, where the main olive-growing regions are Andalusia, Extremadura and Castilla La Mancha [37].…”
Section: Olive Tree Cultivationmentioning
confidence: 99%
“…As we can observe, world production has doubled. This is due to the balanced composition of the oil and its link with greater longevity and lower cardiovascular disease rate, cancer and age cognitive decline [44][45][46]. The trend in international production is marked by Spanish production, where the main olive-growing regions are Andalusia, Extremadura and Castilla La Mancha [37].…”
Section: Olive Tree Cultivationmentioning
confidence: 99%
“…Given that most previous studies on olive oil consumption and cognition were conducted in Mediterranean countries, 7 , 8 , 9 , 10 studying the US population, where olive oil consumption is generally lower, could offer unique insights. Recently, we showed that olive oil consumption was associated with a lower risk of total and cause-specific mortality in large US prospective cohort studies, including a 29% (95% CI, 22%-36%) lower risk for neurodegenerative disease mortality in participants who consumed more than 7 g/d of olive oil compared with little or none.…”
Section: Introductionmentioning
confidence: 99%
“…5 A substudy conducted as part of the Prevencion con Dieta Mediterranea (PREDIMED) randomized trial provided evidence that higher intake of olive oil for 6.5 years combined with adherence to a Mediterranean diet was protective of cognitive decline when compared with a low-fat control diet. [6][7][8] Given that most previous studies on olive oil consumption and cognition were conducted in Mediterranean countries, [7][8][9][10] studying the US population, where olive oil consumption is generally lower, could offer unique insights. Recently, we showed that olive oil consumption was associated with a lower risk of total and cause-specific mortality in large US prospective cohort studies, including a 29% (95% CI, 22%-36%) lower risk for neurodegenerative disease mortality in participants who consumed more than 7 g/d of olive oil compared with little or none.…”
Section: Introductionmentioning
confidence: 99%